The Correlation between Chemotherapy (Vesikan) and Extravasation in Cancer Patients in Teguh Pure Hospital in 2018 - Seriga Banjarnahor (Institute of Computer Science (IOCS), 2018)
Patients with cancer will usually be on a long and repeated course of treatment. Specific and systemic drugs are needed to kill cancer cells such as vesikan drugs that have the side effect of extravasation. The purpose of this study was to determine the relationship of chemotherapy drug administration (vesikan) with extravasation events in cancer patients. This type of research is a correlational analytic study with a cross sectional approach. The research was conducted at Murni Teguh Hospital, Medan. The population in this study were 611 people and 10% samples were taken, 61 people. Data were analyzed univariately and bivariately using the chi-square test with a confidence level of 95% ( = 0.05). The research results are pointingThe majority of respondent drug types are Adriamycin (doxorubicin) (90.2%), minority of respondent drug types are Methotrexate (1.6%). ). The administration of chemotherapy drugs (vesikan) is significantly related to the incidence of extravasation in cancer patients in Medan Teguh Pure Hospital in 2018, p-value 0.004 <0.05. It is recommended to nurses to pay more attention to the results of giving chemotherapy drugs to patients and the effects that may arise such as extravasation. Nurses also need to provide health education to cancer patients about the drugs to be given so that patients are better prepared to deal with the side effects of chemotherapy for prescription drugs.